2016
DOI: 10.1007/s12011-016-0648-9
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Aluminum Chloride on Kidney of Rats

Abstract: This study investigated the toxicity of aluminum chloride (AlCl3) exposure in the rat kidney. Forty male Wistar rats (5 weeks old), weighing 110-120 g, were randomly divided into four groups: control group (CG, 0 g/L AlCl3), low dose group (LG, 0.4 g/L AlCl3), mid dose group (MG, 0.8 g/L AlCl3), and high dose group (HG, 1.6 g/L AlCl3). Rats were administered AlCl3 in their drinking water for 120 days. A variety of measurements were taken including superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…Yang et al, 2017, proved that the inflammatory cytokines have a stimulating effect on the accumulation of neutrophils to increase the injury of inflammation in the liver tissue. The present results are also in harmony with liu et al, 2016 andHammad, 2018, who found an increase in TNF-α and IL-6 in the liver and kidney of rats treated with AlCl3.…”
Section: Discussionsupporting
confidence: 92%
“…Yang et al, 2017, proved that the inflammatory cytokines have a stimulating effect on the accumulation of neutrophils to increase the injury of inflammation in the liver tissue. The present results are also in harmony with liu et al, 2016 andHammad, 2018, who found an increase in TNF-α and IL-6 in the liver and kidney of rats treated with AlCl3.…”
Section: Discussionsupporting
confidence: 92%
“…Al causes a wide range of toxicity in the nervous, hematopoietic, skeletal, respiratory, and immune systems (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Rats were obtained from El Osman Farm, Cairo, Egypt, housed in stainless steel cages, and provided with food, water, and libitum . Aluminum chloride was received daily at a dose of 1.6 ml/l added to the drinking water ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%